Influence of Heating Rate on the Transformation Temperature Change in Selected Steel Types - Moravec, Jaromir; Novakova, Iva; Vondracek, Jiri (Manufacturing Technology Journal, 2020)
The paper is focused on the polymorphic transformations of selected steel types. Generally, when creating CCT diagrams, the transformation temperature values Ac1 and Ac3 are determined under at very low heating rates (max. 0.1 °C?s-1). The only exceptions are so-called in-situ CCT diagrams, which are determined based upon the real temperature cycles. However, in the case of dynamic processes such as welding technology or heat treatment with magnetic induction heating, cannot be used information from conventional CCT diagrams. Incorrectly selected temperatures lead either to incomplete austenitizing during heat treatment or to a different development of phase transformations in HAZ of welds. Especially, when these processes are carried out without soaking temperature. That is why as the main aim of this paper was to determine the heating rate influence for steels S460MC, S690QL and X23CrMoV12-1 on the shift of their transformation temperatures Ac1 and Ac3. The in-tensity of the heating rate effect on the transformation temperature depends on the steel structure and amount of alloying elements. Consequently, steels with different structures, different type of processing and mechanical properties were deliberately selected to make the assessment as complex as possible.
Keywords: Thermal cycle; Heating rate; Transformation temperature; CCT diagram